Claiming New Spaces for Curriculum Studies: Working to “unconceal what is hidden” - Krasny, Karen A.; Brushwood Rose, Chloe; Tremblay, Taunya (Journal of the Canadian Association for Curriculum Studies, 2012)
The editorial for volume 10, number 1, 2012.